Learning Disabled students Before, During and After the rehabilitation tool; The Application of Repeated Measures of Analysis of Variance (Remanova) - Puspa Liza, Ghazali; Nik Hazimi, Mohammed Foziah; Wan Mohamad Asyraf, Wan Afthanorhan; Abdul Malek, A Tambi; Mustafa, Mamat; Lazim, Omar; Roslida, Abdul Razak (2019)
A clinical work was done among six students from Malaysian primary schools. Three of them were normal students and the other three were learning disabled students. The purpose of the clinical work is to see whether private class, parenting advice and food supplements, which were provided for the chosen students, can give a significant different in learning disabled students before and after the clinical work. Assessing by the test scores of Malay language and Mathematics, the clinical work was a success due to the learning disabled students able to show significant improvement before and after the clinical work. Hence, private class, parenting advices and food supplement can be used as the rehabilitation tools for learning disabled students in helping them to learn well as their normal peer.